Validity and Reliability of the Spiritual Counselling Intervention Module (MIKS) - Nor Asliza Mohd Zin; Ku Suhaila Ku Johari; Abu Yazid Abu Bakar; Mohd Izwan Mahmud (Qubahan Academic Journal, 2024)
This study aims to determine the validity and reliability of the Spiritual Counselling Intervention Module (MIKS) for secondary school students. This study aims to develop a counselling module based on a spiritual approach, namely the 'Spiritual Counselling Intervention Module (MIKS) based on the Tazkiyah al-Nafs al-Ghazali Model, to deal with mental health issues. This module is based on the Tazkiyah al-Nafs model by Imam Ghazali. In carrying out this study, the design and development method (Design and Development Research, DDR) was used according to three systematic phases, namely Phase 1: analysis of needs; Phase 2: design and development; and Phase 3: evaluation and usability. Validity tests are conducted based on evaluations from experts in various fields involving psychologists, guidance and counselling experts, and religious experts. The reliability test was conducted on 60 high school students in four schools. The results show that the overall reliability coefficient of this module is very high (Cronbach Alpha = 0.978). Feedback from respondents to the module was positive. This study can help develop a counselling module related to religion and spirituality to help counsellors in dealing with psychosocial issues and mental well-being, especially in dealing with the problem of depression among secondary school students, correct the spiritual element that is the cause of problems in everyday life.